Pendampingan Administrasi Sekolah berbasis Digital di SMP Muhammadiyah Palangka Raya: Digital-based School Administration Assistance at Muhammadiyah Middle School Palangka Raya - Surawan Surawan; Mazrur Mazrur; Rodhatul Jennah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Technological developments have a significant impact, one of which is education. Activities or services in schools that were initially manual are now turning digital. Of course, this also requires preparation from various components of the school, both students and educators. This service aims to help schools with digital services. The method is a mentoring method with an approach in this service using the PAR or Participatory Action Research approach. The results of this dedication activity are: Improving quality, broadening insight, knowledge, and skills for educators and education staff at Muhammadiyah Junior School of Palangka Raya through community service activities related to school administration governance and providing strengthening the implementation of school administration governance by both lecturers and students. Produced 2 Microsoft Exel-Based School Administrative Governance Applications, the PPDB EMIS and DAPODIK Applications, and the Lahajar v.4.4 Application.